3D hierarchical golden wattle-like TiO2 microspheres: polar acetone-based solvothermal synthesis and enhanced water purification performance. Issue 16 (31st March 2017) - Sun, Xiang; Xu, Shiping; Gao, Yuan; Yue, Min; Yue, Qinyan; Gao, Baoyu
Abstract : A polar solvent (acetone)-based solvothermal reaction was successfully used to synthesize highly efficient 3D hierarchical golden wattle-like TiO2 microsphere structures. Abstract : 3D hierarchical TiO2 microsphere structures self-assembled from 1D nanostructures have attracted considerable research attention due to their unique microstructures and properties, and non-polar solvent-based solvothermal methods have been proved to be effective techniques to synthesize such structures. However, to the best of our knowledge, no successful products have been reported based on polar solvents in the available literature. Herein, for the first time, uniform and sophisticated golden wattle ( Acacia pycnantha )-like TiO2 microsphere structures, self-assembled from highly crystallized and radially grown 1D rutile nanorods, were successfully synthesized via a template-free solvothermal reaction using only polar acetone as the solvent in the presence of hydrochloric acid (HCl). The obtained samples showed good water purification performance, even superior to Degussa P25, owing to their unique 1D nanorod building block structure, fast electron transfer rate, excellent light harvesting capability and good crystallinity. In addition, a three-step growth mechanism of the golden wattle-like TiO2 microspheres was proposed based on a time-dependent morphology and crystal form evolution process. The synthetic strategy for the golden wattle-like TiO2 microspheres employed in this study provides new insights into the design of 3D hierarchical TiO2 structures for practical environmental purification applications.